A study of genital human papillomavirus (HPV) infection and antibody response in heterosexually active South African couples - Mbulawa, Zizipho Ziphozakhe Anita (Division of Virology, 2015)
This study constitutes the first report on type-specific human papillomavirus (HPV) concordance and transmission in heterosexually active couples that are human immunodeficiency (HIV)-seronegative, HIV-seropositive or HIV-discordant and in which 71% of female participants have normal cervical cytology.